2007
DOI: 10.7150/ijbs.3.380
|View full text |Cite
|
Sign up to set email alerts
|

Versican Expression during Synovial Joint Morphogenesis

Abstract: The extracellular matrix (ECM) plays a critical role in governing cell behavior and phenotype during limb skeletogenesis. Chondroitin sulfate proteoglycans (Cspgs) are highly expressed in the ECM of precartilage mesenchymal condensations and are important to limb chondrogenesis and cartilage structure, but little is known regarding their involvement in formation of synovial joints in the embryonic limb. Matrix versican Cspg expression has previously been reported in the epiphysis of developing long bones and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
26
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 35 publications
(45 reference statements)
5
26
0
Order By: Relevance
“…Type I collagen and versican were prominently expressed in the AF and developing longitudinal ligaments and therefore more representative of cell populations found in fibrous tensional connective tissues (Lebaron 1996;Margolis and Margolis 1994;Zimmermann 2000). Versican is also highly expressed in the presumptive inter-zone of developing synovial joints during early stages of morphogenesis (Shepard et al 2007), and can modulate cell signalling (Rahmani et al 2006;Wight 2002;Wu et al 2005) which is consistent with the localisation of versican in the IVD inter-space in the present study. Furthermore, versican G3 domain also enhances cellular adhesion and proliferation of intervertebral disc cells in vitro (Yang et al 2003) thus it may influence the recruitment, proliferation and differentiation of chondrogenic cells for IVD assembly.…”
Section: Discussionsupporting
confidence: 90%
“…Type I collagen and versican were prominently expressed in the AF and developing longitudinal ligaments and therefore more representative of cell populations found in fibrous tensional connective tissues (Lebaron 1996;Margolis and Margolis 1994;Zimmermann 2000). Versican is also highly expressed in the presumptive inter-zone of developing synovial joints during early stages of morphogenesis (Shepard et al 2007), and can modulate cell signalling (Rahmani et al 2006;Wight 2002;Wu et al 2005) which is consistent with the localisation of versican in the IVD inter-space in the present study. Furthermore, versican G3 domain also enhances cellular adhesion and proliferation of intervertebral disc cells in vitro (Yang et al 2003) thus it may influence the recruitment, proliferation and differentiation of chondrogenic cells for IVD assembly.…”
Section: Discussionsupporting
confidence: 90%
“…Additional reports demonstrate a versican-rich ECM promotes mesenchymal cell proliferation (Shepard et al, 2007; Shibata et al, 2003; Snow et al, 2005). Versican accumulation is also associated with intimal hyperplasia where vascular smooth muscle cells (VSMC) proliferate (Wight, 2008); conversely, as the intimal lesion regresses, versican is cleaved concomitant with quiescence of VSMC (Kenagy et al, 2005; Kenagy et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…Nguyen et al found that stem cell differentiation could be spatially regulated based on the inclusion of various glycosaminoglycans into poly(ethelene glycol)-diacrylate hydrogels (21). During embryogenesis, a variety of CS sulfation patterns are distributed in specific spatiotemporal patterning (22)(23)(24). Additionally, aggrecan, a proteoglycan with a high CS-containing domain, is found in abundance in mature articular cartilage.…”
Section: Discussionmentioning
confidence: 99%